1972
DOI: 10.1084/jem.136.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Adjuvants and the Mechanism of Cell Cooperation

Abstract: Immunological adjuvants are defined as agents which act nonspecifically to enhance immune responsiveness to a specific antigen. While many substances are known to have adjuvanticity, remarkably little is understood about the mechanism by which they enhance either the antibody response or cellular immunity. It is now clear, for at least some antigens, that interaction of three cell types is required for antibody formation: thymus-derived lymphocytes (T cells), bone marrow-derived lymphocytes (B cells), and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 9 publications
(2 reference statements)
1
18
0
Order By: Relevance
“…In order to be activated, the B cell apparently needs more than one signal: two or more molecules of antigen cross-linked by anticarrier antibody (25) or by anticarrier T cells, these being then linked to the B cell through the antigen (26). In some instances, however, the second signal does not originate in the antigen under study; T cells might act on B cells either directly as in the allogeneic effect (22,23) or through the liberation of a mediator induced by their interaction with any antigen to which they are sensitized (21,24). These interpretations must be accepted with caution, inasmuch as they are inferred from complex systems in which cross-reactivity between antigens might furthermore exist.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In order to be activated, the B cell apparently needs more than one signal: two or more molecules of antigen cross-linked by anticarrier antibody (25) or by anticarrier T cells, these being then linked to the B cell through the antigen (26). In some instances, however, the second signal does not originate in the antigen under study; T cells might act on B cells either directly as in the allogeneic effect (22,23) or through the liberation of a mediator induced by their interaction with any antigen to which they are sensitized (21,24). These interpretations must be accepted with caution, inasmuch as they are inferred from complex systems in which cross-reactivity between antigens might furthermore exist.…”
Section: Discussionmentioning
confidence: 80%
“…Carrier and hapten determinants are unrelated, separate determinants (14, 17); this conclusion is strongly favored by experiments where tolerance to the carrier reduces the response to the hapten (13,18,19). Carrier and hapten determinants must be on the same molecule (14,17,20), although recent reports challenge this conclusion (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 81%
“…Maillard and Bloom reported that tubercle bacilli affect T cells which produce the soluble factor(s) which mediates the adjuvant effect [34]. More recently, Mitchell et al have shown that BCG cells nonspecifically enhanced cell-mediated cytotoxicity in which T cells are effector cells [38].…”
Section: The Failure Of Bcg-cws To Substitute For Macrophages and T Cmentioning
confidence: 99%
“…Maillard and Bloom suggested that pertussis and tubercle bacilli act on T cells, resulting in soluble factor(s) being released from T cells and capable of exerting an adjuvant effect [34]. In this report, we have tried to elucidate whether the cell wall of BCG stimulates the humoral responses against SRBC and hapten-protein conjugate and have also tried to identify the type of cell responsible for the adjuvant effect using the in vitro culture system.…”
mentioning
confidence: 99%
“…Many experiments have been performed to show that DTH reactions can result in nonspecific enhancement of in vitro humo ral immune responses [11,15]. This phe nomenon is thought to be related in some way to the mechanisms of action of adju vants and may provide possible explana tions for some functions of adjuvants.…”
Section: Introductionmentioning
confidence: 99%